2013
DOI: 10.1073/pnas.1221999110
|View full text |Cite
|
Sign up to set email alerts
|

Interference with ERK Thr188 phosphorylation impairs pathological but not physiological cardiac hypertrophy

Abstract: Extracellular signal-regulated kinases 1 and 2 (ERK1/2) are central mediators of cardiac hypertrophy and are discussed as potential therapeutic targets. However, direct inhibition of ERK1/2 leads to exacerbated cardiomyocyte death and impaired heart function. We have previously identified ERK Thr188 autophosphorylation as a regulatory phosphorylation of ERK1/2 that is a key factor in cardiac hypertrophy. Here, we investigated whether interference with ERK Thr188 phosphorylation permits the impairment of ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 46 publications
(66 reference statements)
1
75
0
Order By: Relevance
“…MAPKs family, one of the most important downstream signal pathways of oxidative stress, is also involved in cardiomyocyte hypertrophy (Ruppert et al, 2013). Previous researchers found that generation of ROS and activation of ERK were augmented in cardiomyocyte hypertrophy induced by Ang II, a-adrenoceptor agonists, or endothelin-1 in vitro, as well as in pressure overload-induced cardiac hypertrophy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs family, one of the most important downstream signal pathways of oxidative stress, is also involved in cardiomyocyte hypertrophy (Ruppert et al, 2013). Previous researchers found that generation of ROS and activation of ERK were augmented in cardiomyocyte hypertrophy induced by Ang II, a-adrenoceptor agonists, or endothelin-1 in vitro, as well as in pressure overload-induced cardiac hypertrophy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ERK autophosphorylation, which requires the activation and assembly of the entire Ras-ERK cascade and dimerization of ERK is a critical event in the induction of ERK-mediated cardiac hypertrophy in response to various stimuli (Lorenz et al, 2009). ERK2 T188A , which is DN for ERK Thr188 signaling, attenuated cardiomyocyte hypertrophic responses to phenylephrine (PE) and to chronic pressure overload in isolated cells and intact hearts without any effect on anti-apoptotic ERK1/2 signaling and physiological cardiac function (Ruppert et al, 2013). Interestingly, despite inhibition of pathological hypertrophy, ERK2 T188A did not affect physiological cardiac growth associated with age or exercise, therefore, suggesting that interference with ERK Thr188 phosphorylation may be a selective therapeutic strategy in pathological ERK1/2-mediated cardiac hypertrophy.…”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…Phosphoinositide 3 kinase (PI3K)[p110γ] is also activated by GPCR pathways and negatively regulates cardiomyocyte contractility by modulating the activity of phosphodiesterases (PDEs) and cAMP [11]. Recent studies have uncovered new findings related to the role of calcineurin and CaMKII in the heart [12], as well as the complexities surrounding activation of extracellular signal-regulated kinases (ERK1/2) at two distinct phosphorylation sites via G protein subunits [13]. Further, some of the molecules implicated in these pathways have been the targets of pharmaceutical development which will be discussed in this review.…”
Section: Pathological Cardiac Hypertrophymentioning
confidence: 99%